Open Access: An analysis of European publisher copyright and licensing policies today - Labastida i Juan, Ignasi (Septentrio Conference Series, 2020)
See RECORDING. The digital age has brought authors of publications many more opportunities to gain further impact and visibility by sharing their work online through websites, pre-print servers, repositories, publishing platforms or other digital venues as well as journals. Publisher copyright policies have not always been enablers of these new practices but change is underway. Europe has also seen a surge in international, national and local Open Access (OA) policies in recent years, a significant one being Plan S with its requirements related to rights retention and open licensing. How far are publishers in supporting authors in this change? In early 2020 SPARC Europe commissioned a report to gain a better understanding of current copyright and licensing practices amongst scholarly journal publishers based in Europe and how these are presented to academic authors. The key purpose of the study was to provide evidence on how publisher policies support OA and to see whether the complexity of the copyright and self-archiving landscape amongst publishers has simplified over time. We also explored how Plan S-ready publishers were with regards to the first principle of their policy related to authors or their institutions being required to retain copyright to their publications, calling for all publications to be published under an open license, preferably CC BY, immediately and under no embargo. Research was undertaken on various levels: the 2020 study reviewed the copyright, self-archiving and open licensing policies from 10 large legacy publisher websites and then asked these publishers to verify these findings. We also analysed the policies of pure open access journals in Europe from the Directory of Open Access Journals (DOAJ). To limit the scope, Europe was taken as the focus of this research. This paper will firstly demonstrate how diversely publishers present and share information on their copyright, licensing and self-archiving policies and how challenging this can be for authors and the institutions that support them. We will also share findings on the specifics of publisher policies be they hybrid or pure OA. For example, examining how far large publishers currently allow authors to retain publishing rights for articles, to what extent they allow zero embargoes when self-archiving or how far pure OA journals use the CC BY license. This paper ends by making a number of recommendations to publishers, research funders, institutions and authors to ultimately support authors to more easily navigate this policy landscape and to be able to publish immediate OA.